Achieving university libraries user loyalty through user satisfaction: the role of service quality. Issue 1 (2nd January 2022) - Twum, Kojo Kakra; Adams, Matilda; Budu, Stephen; Budu, Rosina Akuokor Anati
ABSTRACT: This study examines the influence of library service quality dimensions (i.e. service affect, information access, library as place, and personal control) on user satisfaction, as well as user satisfaction on user loyalty. Data were drawn from 349 library users from a public university library in Ghana. The hypothesized relationships were analyzed using structural equation modeling. The study revealed that with the exception of library as place all the service quality dimensions had a positive significant relationship with library user satisfaction. The study further established a positive significant relationship between user satisfaction and user loyalty. The practical implication is that the attainment of library user loyalty is possible when the management of libraries improve the level of user satisfaction with services. This study is one of the few on assessing library service quality, customer satisfaction, and user loyalty in a developing country context.